Genotypic correlation and path analysis of kale half‑sib progenies - Azevedo, Alcinei Mistico; Seus, Rogério; Gomes, Cristiane Lourenço; Freitas, Elis Marina de; Candido, Diego Mattos; Silva, Derly José Henriques da; Carneiro, Pedro Crescêncio Souza (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the associations between traits in half‑sib families of kale, through genotypic correlation and path analysis, and possible effects of truncated selection. Thirteen traits were evaluated in 24 half‑sib families of kale. Four path analysis were carried out, considering the following basic variables: plant height, number of shoots, number of leaves per plant, and stem diameter. Each analysis included 12 traits as explicative variables. The highest estimates of correlation were found between the following traits: length and width of petioles; number of leaves; leaf fresh weight; and length and width of the leaves. The selection for the smallest number of shoots leads to a reduction of petiole length; for the highest number of leaves, selection provides the increase of leaf fresh weight and the reduction of fresh weight per leaf; and, for the largest stem diameter, selection causes the production increase of fresh leaf weight. The truncated selection for plant height does not cause significant changes in the other evaluated traits.